Firm Value Factors: The Effect of Earning Per Share, Capital Structure, and Dividend Policy on Creative Business Companies - Effendi, Bahtiar (LLDIKTI Wilayah 1 Sumatera Utara, 2023)
Firm value is one of the measurements used to gain investor and creditor confidence. A high company value will make investors believe in investing their capital or investing in a company, because a high company value indicates good company performance and is a measure of the high level of shareholder prosperity indirectly. This study aims to determine whether there is an influence between earnings per share (EPS), capital structure, and dividend policy on firm value. The companies studied are creative business companies listed on the Indonesia Stock Exchange in 2019 – 2022. This research is a quantitative study. The population in this study were consumer goods companies and the sample method used was purposive sampling. The data analysis technique used is descriptive statistics, multiple linear regression analysis, coefficient of determination (R2), partial test (t test) and simultaneous test using SPSS version 26.00. The results of the study found that earnings per share has a significant effect on firm value, dividend policy has a significant effect on firm value, capital structure has no effect on firm value. The result of futher research found that earning per share, capital structure, and dividend policy simultaneously has a significant impact on firm value.